The Effectiveness of the Implementation of Law No. 16 of 2019 in the Prevention of Early Marriage: A Field Study at KUA Cibeureum - Yanti Haryanti (Bulletin of Islamic Research, 2025)
Marriage is an innate bond that is expected to last a lifetime until death separates. The problem of marriage that until now is still widely violated and has become a problem in society is underage marriage. After the amendment of the Marriage Law, the age limit for marriage is equalized between women and men, which is a minimum of 19 years. This change aims to increase public awareness about the impact of underage marriage. Ensuring public understanding of marriage procedures and requirements in accordance with Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. The method uses an empirical or sociological juridical approach, namely analyzing law in practice in society, including data collection by interviewing, observation, and study of legal documents, analyzing data by comparing legal theory with practice in the field, and compiling research results that can be used for more effective legal development. The results of the first field study due to underage marriage include, Health: Female Reproductive Disorders of Pregnancy and even feared to cause death in mothers and children. Children's education: Children under 19 years old are of school age so they are not yet suitable for marriage, Economics: One of them is Labor productivity has decreased because many individuals do not have adequate skills or education. Psychological Field: Lack of emotional readiness in dealing with home life can increase the risk of depression, they also tend to lose adolescence and freedom, which can make them feel isolated. High divorce rates. Protection of children: Because they are not yet fit to get married, to avoid domestic problems in the future. Second, the community better understands the change in the age limit for marriage, namely for men and women equal to 19 years.